2018
DOI: 10.1111/jocn.14376
|View full text |Cite
|
Sign up to set email alerts
|

Psycho‐cognitive predictors of burnout in healthcare professionals working in emergency departments

Abstract: These results might be used to develop tailored psycho-educational interventions. This might help healthcare professionals to develop personal skills to cope with the critical conditions that characterise their work and to enable them to recognise potential risk factors that favour burnout. This has pivotal implications for the maintenance of the patient-healthcare professional relationship and in reducing clinical errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
34
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 32 publications
4
34
0
4
Order By: Relevance
“…Difficulties in emotional regulation exposed ER nurses to high levels of emotional exhaustion, depersonalization and lack of personal accomplishment. This is consistent with findings from international literature (Donoso et al, ) and with a recent Italian study (Masiero et al, ) which found a positive correlation between ER nurses’ burnout and their difficulties to verbalize and manage own feelings (alexithymia).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Difficulties in emotional regulation exposed ER nurses to high levels of emotional exhaustion, depersonalization and lack of personal accomplishment. This is consistent with findings from international literature (Donoso et al, ) and with a recent Italian study (Masiero et al, ) which found a positive correlation between ER nurses’ burnout and their difficulties to verbalize and manage own feelings (alexithymia).…”
Section: Discussionsupporting
confidence: 93%
“…A large body of literature (e.g., Arnold, Connelly, Walsh, & Martin Ginis, 2015;del Carmen Pérez-Fuentes, Mar Molero-Jurado, Gázquez-Linares, & Mar Simón-Márquez, 2019;Fornés-Vives, García-Banda, Frias-Navarro, & Pascual-Soler, 2019) has explored the relationship between burnout and emotional characteristics like emotional intelligence, emotional labour and emotion regulation. A recent Italian study (Masiero, Cutica, Russo, Mazzocco, & Pravettoni, 2018) have highlighted that the ER health care professionals who had difficulties to verbalize and manage their feelings were more prone to burnout.…”
mentioning
confidence: 99%
“…Studies that evaluated stressors related to the work of the nursing team in emergency care evidenced work-related fatigue and musculoskeletal disorders. As well as the presence of higher emotional exhaustion scores associated with depression, anxiety, traumatic experience and perceived stress (21)(22)(23) .…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to develop educational interventions in the work environment. These actions can help health professionals develop personal skills in dealing with the critical conditions characteristic of their work and enable them to recognize potential risk factors that favor occupational stress (22) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation